2020
DOI: 10.1002/app.49183
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crystallization on microcellular foaming behavior of polyamide 6 in a supercritical CO2‐assisted route

Abstract: Supercritical CO2 as a blowing agent has attracted increasing interest in the preparation of microcellular polyamide 6 (PA6) foams. In this work, we developed the supercritical CO2‐assisted method to prepare a series of different microcellular PA6 foams by controlling its crystallization properties in two steps and carefully investigated the corresponding crystallization properties of modified PA6 and foams using various techniques. Initially, a multifunctional epoxy‐based chain extender (CE) was used to produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…In recent years, the microcellular foaming composites are increasingly recognized as an important component for improving the structure and properties of polymeric materials due to their remarkable effects such as lightweight [ 1 , 2 , 3 ] and low dielectric constant [ 4 , 5 ]. The microcellular foaming process can generate large numerous of micron-sized cells inside the polymer matrix, forming a unique dense surface and core foamed structure [ 6 , 7 , 8 ]. This structure could reduce the weight of the material, and it endows the material with higher toughness, impact strength, and dimensional accuracy [ 9 , 10 , 11 , 12 , 13 ], which is meaningful to the requirement of lightweight.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the microcellular foaming composites are increasingly recognized as an important component for improving the structure and properties of polymeric materials due to their remarkable effects such as lightweight [ 1 , 2 , 3 ] and low dielectric constant [ 4 , 5 ]. The microcellular foaming process can generate large numerous of micron-sized cells inside the polymer matrix, forming a unique dense surface and core foamed structure [ 6 , 7 , 8 ]. This structure could reduce the weight of the material, and it endows the material with higher toughness, impact strength, and dimensional accuracy [ 9 , 10 , 11 , 12 , 13 ], which is meaningful to the requirement of lightweight.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the PTFE nanofibrils network was effective cell nucleating agent. However, according to our knowledge, only a few reports on polyamide 6 foam using batch foaming method assist by scCO 2 were reported 14,15,35,36 . The influence of PTFE in PA6 foams was unclear.…”
Section: Introductionmentioning
confidence: 96%
“…The low melt strength of the pure PA6 with linear molecular chain structure limit its foaming ability 14–16 . To improve the PA6 melt strength, the chain extending modification usually was used 15,17–21 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations